Hierarchical and Polycentric Leadership in the Church on Congregation Participation - Frederich Oscar Lambertus Lontoh (Moriah Theological Seminary, 2026)
AbstractThe church leadership structure is a critical factor influencing congregational involvement. The traditional hierarchical model, which centers on a single authoritative figure, is now widely questioned for its effectiveness in empowering the active participation of all members of the body of Christ. As an alternative, a polycentric (distributed) leadership model that distributes authority based on gifts and functions is increasingly being adopted. However, claims regarding the relative effectiveness of the two models in encouraging congregational participation require systematic study. This study uses a qualitative comparative literature review method. The primary data sources consist of scientific journal articles. The analysis was conducted thematically to identify, compare, and synthesize findings regarding the definition, implementation, and impact of each model on indicators of congregational participation. The study reveals fundamental differences in the philosophy and impact of the two models. Hierarchical leadership tends to create efficiency in decision-making and maintain doctrinal stability, but often limits participation to the implementation of predetermined programs. Conversely, polycentric leadership is significantly more effective in encouraging initiative, creativity, and a sense of ownership among congregations toward ministry. Its success depends heavily on a culture of mutual trust, a clear disciplinary system, and a commitment to nurturing gifts. However, the polycentric model also faces challenges such as potential conflict, slow decision-making, and the need for more intensive coordination. This study concludes that there is no “one size fits all” model. Hierarchical leadership may remain relevant in contexts that require high stability and uniformity, while polycentric leadership excels in building empowering and adaptive communities. The practical implication for the church is the need for a contextual hybrid leadership design that takes the principle of gift distribution from the polycentric model without completely disregarding the clarity of accountability from hierarchical structures. Further research is needed to explore this hybrid model in various denominational and cultural settings.